Kesalahan Penggunaan Jouken Hyougen Pada Pembelajar Bahasa Jepang Level Menengah ATAS - Gilang Auliya Prasetyo Widodo; Dedi Sutedi (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2020)
This study discusses the mistake of the jouken hyougen in advanced-level Japanese language learners. Therefore the research aims to find out what mistakes are often experienced by upper-middle Japanese language learners in understanding the use of jouken hyougen to,tara, nara, dan ba. Then this study aims to provide advice or efforts to minimize mistakes using jouken hyougen. The method used in this research is descriptive qualitative. Data collection was carried out using test and interview instruments. The form of test questions is a test to translate as many as 5 questions and a test of true or false as many as 5 questions which include jouken hyougen of to, tara, nara, and ba. Then after the test ends, interview the respondent to find out why the respondent is wrong in answering the questions given. The subjects of this study were Japanese middle-level Japanese language learners. They are advanced learners with level 3 to level 1 Japanese language skills (JLPT). Based on the data that has been obtained, it is known that middle-level learners still often experience errors. As in the use of tara to show presuppositions related to time and this condition of presupposition related to time are wrong if used word moshi. The error has a percentage of errors of 86.4% or 32 people from a total of 37 respondents answered incorrectly. In the use of the form ba and to which shows something that is natural, the respondent is considered quite good in understanding the use of the supposition ba and to. From the test data that has been tested only 16.2% or 6 people out of a total of 37 respondents answered incorrectly. Based on the results of interviews with respondents, admitted that they did not know the rules that apply to every form of presupposition of to, tara, nara, and ba. Efforts that can be made to minimize mistakes are as instructors to optimize understanding of spending on the material jouken hyougen, motivates learners to find out for themselves from various sources outside the book obtained during learning, then ask the native speaker if you want to know when the context of jouken hyougen to, tara, nara, and ba is used.